Antimicrobial Susceptibility of Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli Isolated from Mastitic Dairy Cattle in Ukraine - Leta Elias; Ajay S. Balasubramanyam; Olena Y. Ayshpur; Iryna U. Mushtuk; Nataliya O. Sheremet; Volodymyr V. Gumeniuk; Jeffrey M. B. Musser; Artem S. Rogovskyy (MDPI AG, 2020)
Bovine mastitis is the predominant cause for antimicrobial use on dairy farms and is a major source of economic losses in the dairy industry. In this study, the antimicrobial susceptibility profiles of common mastitis-causing pathogens, Staphylococcus aureus (n = 62), Streptococcus agalactiae (n = 46), and Escherichia coli (n = 129), were determined for dairy cattle with mastitis across 142 Ukrainian farms. The results showed that there were more gentamicin resistant S. aureus isolates (16.95%) identified in this study than previously reported for Ukrainian dairy cattle. Moreover, low levels of amoxicillin susceptibly (13.51%) were observed for St. agalactiae, which contrasted a previous study showing susceptibility levels of >50%. St. agalactiae resistance to tetracycline was observed in 80% of the isolates. Cephalosporin use was most ineffective against E. coli, with 43.27-56% of the isolates exhibiting this resistant trait. Overall, this study performed a preliminary analysis of antimicrobial resistance on mastitis isolates from Ukrainian farms. However, given the limited numbers of the isolates tested in this study and that the publications on antimicrobial resistance in animal husbandry of Ukraine are very few, more extensive investigations are needed to comprehensively examine susceptibility patterns of mastitis-causing pathogens in dairy cattle in Ukraine.